A Legal Framework for Data Intellectual Property Registration: Theoretical Basis and Practical Pathways - Luo, Han; Zhang, Yiqing (Technium Social Sciences Journal, 2025)
The existing paradigms of data intellectual property registration largely inherit from past practices in literary and industrial property rights, attempting to replicate the exclusive-control-oriented logic of information property rights through isomorphic mechanisms. However, as registration objects, data collections are characterized by instability and relative exclusivity, making them more suited to a framework of mutual benefit-sharing rather than exclusive control in terms of empowerment and rights confirmation. Consequently, the traditional paradigm of benefit-conferring registration is no longer sustainable. The non-benefit-conferring registration paradigm can address the shortcomings of the Anti-Unfair Competition Law in protecting data rights, balancing both passive defense and proactive utilization, and should be the pathway explored. In terms of systemic positioning, data intellectual property registration is a procedural adjunct rather than a substantive rule, and it must not overstep its bounds or suffer from an unclear nature due to low legal effectiveness hierarchy. In norms construction, it should be compatible with the various protective measures provided by the Anti-Unfair Competition Law, enhancing the certainty of protection and striving to dismantle information barriers in data elementalization allocation. Looking forward, it should maintain a harmonious resonance between substantive and procedural rules, fostering systematic new regulations for data intellectual property.